Short-Term Complications of Anterior Fixation of Odontoid Fractures. Issue 1 (February 2018) - Cutler, Holt S.; Guzman, Javier Z.; Lee, Nathan J.; Kothari, Parth; Kim, Jun S.; Shin, John I.; Leven, Dante M.; Cho, Samuel K.
Study Design: Retrospective study. Objective: Anterior fixation of odontoid fracture has been associated with high morbidity and mortality in small, single institution series. Identifying risk factors may improve risk stratification and highlight factors that could be optimized preoperatively. The objective of this study was to determine the 30-day complication rate following anterior fixation of odontoid fractures and to identify associated risk factors among patients in a large national database. Methods: Patients who underwent anterior fixation were identified in the American College of Surgeons National Quality Improvement Program database (ACS NSQIP) from 2007 to 2012. Patient demographics, medical comorbidities, perioperative complications, and postoperative complications up to 30 days were analyzed by univariate and multivariate analysis. Results: Overall, 103 patients met criteria for the study. The average age was 73.9 years and patients were predominantly white (85.4%). Cardiac comorbidity was common (66.0%), as were dependent functional status (14.6%) and bleeding disorders (13.6%). Complications occurred in 37.9% of patients, and mortality was high (6.8%). Age, white race, and history of bleeding disorders were independently predictive of complications in the multivariate analysis. The postoperative hospital stay was >5 days for 45.6% of patients. Conclusion: In a large, multicenter database study, anterior fixation of odontoid fracture was associated with high morbidity and mortality. Although advanced age was associated with increased risk of complications, patients undergoing anterior fixation were older, on average, than in prior studies. Bleeding disorder was a potentially modifiable risk factor for complications that could be optimized prior to surgery.